Management of Type 2 Diabetes in Stage C Heart Failure with Reduced Ejection Fraction - Anjali Agarwalla; Jadry Gruen; Carli Peters; Lauren Sinnenberg; Anjali T Owens; Nosheen Reza (Cardiac Failure Review)
Type 2 diabetes is an increasingly common comorbidity of stage C heart failure with reduced ejection fraction (HFrEF). The two diseases are risk factors for each other and can bidirectionally independently worsen outcomes. The regulatory requirement of cardiovascular outcomes trials for antidiabetic agents has led to an emergence of novel therapies with robust benefits in heart failure, and clinicians must now ensure they are familiar with the management of patients with concurrent diabetes and stage C HFrEF. This review summarises the current evidence for the management of type 2 diabetes in stage C HFrEF, recapitulating data from landmark heart failure trials regarding the use of guideline-directed medical therapy for heart failure in patients with diabetes. It also provides a preview of upcoming clinical trials in these populations.